Social entrepreneurship practices and social change In Brazil: a qualitative study in three non-governmental organizations - Cavalcanti, Maria Fernanda Rios (2016)
Social Entrepreneurship (SE) has attracted growing interest from a wide variety of actors over the last 30 years, especially due to a general agreement that it could be an important tool for tackling many of the world’s social ills. In the academic sphere, this growing interest did not translate into a matured field of study. Quite the opposite, a quick look at this literature makes it evident that: SE has been consistently subjected to numerous theoretical discussions and disagreements, especially over the definition of the concept of SE which is often based on a taken-for-granted notion of social change; it has been more systematically investigated in restricted contexts, often leaving aside so called developing/emerging countries like Brazil and especially lacking in-depth qualitative studies; SE literature lags behind SE practices and few studies focus on how SE actually occurs in a daily and bottom-up manner. In order to address such gaps, this thesis examines how social entrepreneurship practices accomplish social change in the context of Brazil. In this investigation I conducted an inductive practicebased, qualitative/ethnographic study in three Non-Governmental Organizations (NGOs) located in different cities in the Brazilian state of São Paulo. Data collection lasted from February 2014 until March 2015 and was mainly done through participant observations and through in-depth unstructured conversations with research participants. Secondary data and documents were also collected whenever available. The participants of this study included a variety of the studied organizations’ stakeholders: two founders, volunteers, employees, donors and beneficiaries. Observation data was kept in fieldnotes, conversations were recorded whenever possible and were later transcribed. Data was analyzed through an iterative thematic analysis. Through this I identified eight recurrent themes in the data: (1) structure; (2) relationship with other organizational actors (sub-themes: relationship with state, relationship with businesses and relationship with other NGOs); (3) beliefs, spirituality and moral authority; (4) social position of participants, (5) stakeholders’ mobilization and participation; (6) feelings; (7) social purpose; and (8) social change. These findings were later discussed under the lens of practice theory, and in this discussion I argue and show that, in the context studied: (a) even though SE embraces a wide variety of different social purposes, they are intertwined with a common notion of social change based on a general understanding and aspiration for social equality; (b) this social change is accomplished in a processual and ongoing manner as stakeholders from antagonistic social groups felt compelled to and participated in SE practices. In answering the proposed research question the contributions of this thesis are: (i) the elaboration a working definition for SE based on its relationship with social change; (ii) providing in-depth empirical evidence which accounts for and explains this relationship; (iii) characterizing SE in the Brazilian context and reflecting upon its transferability to other contexts. This thesis also makes a methodological contribution, for it demonstrates how thematic analysis can be used in practice-based studies.